Managing well leakage risks at a geologic carbon storage site with many wells. (September 2019) - Lackey, Greg; Vasylkivska, Veronika S.; Huerta, Nicolas J.; King, Seth; Dilmore, Robert M.
Highlights: Analyzed well leakage risk at a brownfield geologic carbon storage site. Considered several well leakage scenarios and risk mitigation strategies. Used well attribute data to inform monitoring and mitigation decisions. Presented a workflow for determining a risk-based post-injection site care period. Found risk-based well leak mitigation strategy to be robust to uncertainty. Abstract: Potential geologic carbon storage (GCS) sites with a history of oil and gas production have well-characterized injectivity and storage capacity, but the presence of legacy wells increases leakage risk. Thus, the success of GCS operations at sites with many wells will require a thorough leakage risk assessment and a robust strategy for managing well leakage risk over the lifetime of the project. In this study, we demonstrate a workflow that uses the National Risk Assessment Partnership's open-source Integrated Assessment Model to quantify well leakage risks and test the performance of various leakage risk management strategies at a heavily drilled GCS site. Our model simulates a 50-year basin-scale injection of CO2 at a hypothetical site based on the Kimberlina Project Site in the Southern San Joaquin Valley of California. Brine and CO2 leakage through 1000 legacy wells into a USDW are stochastically simulated as a proxy for risk. We consider multiple scenarios that explore the efficacy of various well leakage risk management strategies with changes in well leakage behavior, reservoir behavior, and post-injection site care (PISC) length. Predicted leakage at the site after 100 years was small with a maximum CO2 leakage of 102.1 tonnes (4.08 × 10 −5 % of the 250 Mt injected) and a maximum brine leakage of 2.4 tonnes. Leakage risk management strategies based on accurate prior information about well leak probability reduced leakage risks more effectively at the modeled site and were more robust with respect to reservoir uncertainty than strategies based on the distance of the legacy well from the injector. The importance of the PISC period length was not clear as it had a negligible impact on CO2 leakage risk but a sizable impact on brine leakage risk in our model.